Only doing half the job: Frugivorous birds facilitate the spread but not the germination rate of invasive Cotoneaster pannosus - Karabo T. Moloi; Sandy-Lynn Steenhuisen; Lehlohonolo D. Adams; Colleen T. Downs; Grant D. Martin (South African Journal of Botany, 2024)

Conceptualizing sustainable participation in the context of German football supporters - Sebastian Björn Bauers; Sandy Adam; Michael Fuchs; Leon Piotrowski; Gregor Hovemann (German Journal of Exercise and Sport Research, 2024)
Institutionalized supporter participation is a traditional part of German professional football clubs. Due to commercialization, some challenging issues have arisen in recent years regarding supporter participation. To develop new approaches for improving participation, the study uses a social sustainability perspective, illustrating that social sustainability elements help to develop and structure the potential for improvement of participation in German professional football. By identifying and discussing links between social sustainability and institutionalized supporter participation, we contribute to the conceptualization of sustainable participation. Our research supports the creation of an inclusive and sustainable fan community where fans can actively participate in decisions and actions that affect their current and future fandom environment. Based on the social sustainability principles of health, influence, competence, impartiality, and meaning-making, we compile the following characteristics of sustainable participation: social well-being oriented participation, direct influence, regular voting rights, representative participation, appealable resolutions, information-based participation, barrier-free participation, democratic voting, established constitutions, and encouraged participation. This conceptualization provides approaches and foundations for future investigations regarding participation research in football and practical implications for member associations, association members, league organizers, and other stakeholders to establish and improve institutionalized participation.

Evaluation of two beef cow fixed-time AI protocols that utilize presynchronization - Jaclyn N. Ketchum; Lacey K. Quail; Kaitlin M. Epperson; Chloey P. Guy; Jerica J.J. Rich; Saulo Menegatti Zoca; Adalaide C. Kline; Taylor N. Andrews; Julie A. Walker; Pedro Levy Piza Fontes; Sandy K. Johnson; Megan P.T. Owen; et al. (Theriogenology, 2024)

Seed dispersal by frugivores and germination of the invasive alien shrub Pyracantha angustifolia (Franch.) C.K. Schneid. in Free State Province, South Africa - Lehlohonolo D. Adams; Grant D. Martin; Colleen T. Downs; Vincent R. Clark; Vuyisile Thabethe; Islamiat A. Raji; Sandy-Lynn Steenhuisen (Biological Invasions, 2022)

Asymmetry in information acquisition—Exploring the principal–agent dyad of sport organizations and sport management higher education institutions - Olivia Wohlfart; Sandy Adam; Gregor Hovemann (German Journal of Exercise and Sport Research, 2021)
This study is based on a metaphorical contract in sport management, whereby sport organizations (the principal) engage sport management higher education institutions (the agent) in qualifying graduates according to industry demands. There is asymmetry in the contract due to the lack of incentives for the principal to provide specific information and the agent’s ignorance about this information. A third party can acquire crucial information that sport management higher education institutions need to fulfil the contract. Based on a qualitative content analysis of 12 interviews with sport organization representatives, the study finds that sport management higher education institutions need to focus on either developing generic competencies or credibly signalling the value of sport management-specific competencies in their curriculum in order to efficiently fulfil the contract.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

The March fly and the ant: the unusual pollination system of Eustegia minuta (Apocynaceae: Asclepiadoideae) - Yolanda Chirango; Sandy-Lynn Steenhuisen; Peter V. Bruyns; Jeremy J. Midgley; Adam Shuttleworth (Arthropod-Plant Interactions, 2019)